2014
DOI: 10.1590/s0100-06832014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis mineralógicas preditoras de fontes de produção de sedimentos, em uma bacia hidrográfica do Rio Grande do Sul

Abstract: RESUMOO uso da mineralogia como ferramenta para a avaliação das propriedades dos minerais que compõem o solo é extremamente importante para o entendimento das diferentes relações químicas e físicas que ocorrem nele. Essas propriedades/ variáveis, na identificação das fontes de sedimentos em suspensão, podem ajudar a elucidar os fatores e processos que regem a transferência de sedimentos e poluentes dos sistemas terrestres para os sistemas aquáticos. Os objetivos deste estudo foram caracterizar quantitativament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Studies in watersheds under agricultural production, using fingerprinting technique for source identification of sediment transported in suspension, have been conducted successfully in several countries and have been expanding rapidly (Slimane et al, ; Smith et al, ). Studies were carried out in small rural watersheds in Southern Brazil, in sloping areas cropped mainly with tobacco in small family‐farm units (Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher, Caner, Minella, Bender, et al, ; Tiecher, Caner, Minella, & Santos, ), for no‐till annual crops (Tiecher et al, ), on hillsides with shallow soils and non‐intensive agriculture (Miguel, Dalmolin, Pedron, & Moura‐Bueno, ; Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ), and for urban watersheds (Franz, Makeschin, Wei, & Lorz, ; Poleto, Merten, & Minella, ). For all these agricultural watersheds (Miguel, Dalmolin, Pedron, Moura‐Bueno, et al, ; Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher et al, ), fingerprinting indicated crops and roads as main suspended sediment sources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in watersheds under agricultural production, using fingerprinting technique for source identification of sediment transported in suspension, have been conducted successfully in several countries and have been expanding rapidly (Slimane et al, ; Smith et al, ). Studies were carried out in small rural watersheds in Southern Brazil, in sloping areas cropped mainly with tobacco in small family‐farm units (Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher, Caner, Minella, Bender, et al, ; Tiecher, Caner, Minella, & Santos, ), for no‐till annual crops (Tiecher et al, ), on hillsides with shallow soils and non‐intensive agriculture (Miguel, Dalmolin, Pedron, & Moura‐Bueno, ; Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ), and for urban watersheds (Franz, Makeschin, Wei, & Lorz, ; Poleto, Merten, & Minella, ). For all these agricultural watersheds (Miguel, Dalmolin, Pedron, Moura‐Bueno, et al, ; Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher et al, ), fingerprinting indicated crops and roads as main suspended sediment sources.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a need to identify and quantify the contribution of potential sources of sediment in order to guide the implementation of management measures to mitigate sediment transfer from cultivated hillslopes to water bodies. So far, sediment fingerprinting studies to trace land use contributions conducted in rural areas in Southern Brazil were restricted to small upstream catchments (<20 km 2 ) (Miguel et al, 2014a(Miguel et al, , 2014bMinella et al, 2014Minella et al, , 2009Minella et al, , 2008Minella et al, , 2007Tiecher et al, 2017Tiecher et al, , 2016Tiecher et al, , 2015Tiecher et al, , 2014 (Table 1). Sediment tracing proved to be a powerful technique to identify sediment sources in Brazilian environmental conditions for catchments covered with Acrisols, Cambisols, Chernosols, Gleysols, and Leptosols (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The physical characteristics evaluated were (i) soil resistance to penetration (RP), (ii) gravimetric moisture (GM), and (iii) granulometry (sand, silt and clay). Penetration resistence penetration was determined according to the methodology of Stolf et al (2014), gravimetric moisture and granulometry according to the methodology described by Embrapa (2017).…”
Section: Methodsmentioning
confidence: 99%